(untitled) (The Batuk, 2025)
Digital technology has transformed customer behavior, particularly in the hospitality sector, with online reviews significantly influencing restaurant choices. However, there remains a lack of empirical evidence on how online reviews influence customer choice of restaurants in Nepal. Therefore, drawing on the information adoption model, this study aims to examine the attributes of online reviews influencing customers’ choice of restaurants in Pokhara, Nepal. Using a cross-sectional descriptive design, data were collected from 209 respondents via convenience and snowball sampling. The multiple regression analysis demonstrated three online review attributes (descriptiveness of reviews (β = 0.252, p < 0.05), service quality (β = 0.202, p < 0.10), and ambience of the restaurant (β = 0.198, p < 0.05) influencing customers’ choice of restaurants. However, online review attributes such as overall ratings, number of reviews price, and food and beverage image had no significant effect on customers’ choice. These findings suggest that when choosing restaurants, customers place greater emphasis on qualitative aspects like review content, service experience, and dining atmosphere.